The Impact of Digital Financial Inclusion Implementation and its Implications on Quality Development in Islamic Educational Institutions (A Case Study at Madrasah Tsanawiyah Al Kautsar Depok) - Hariyadi; Ahmad, Gofur; Priharta, Andry (International Journal of Sustainability in Research, 2024)
This research examines the implementation of digital financial inclusion at Madrasah Tsanawiyah Al Kautsar Depok and its implications for quality development. Using a qualitative case study approach, data was collected through interviews, observations, and document analysis. The research explores the implementation process, its impact on financial governance efficiency, and implications for holistic madrasah quality development. Findings reveal a systematic implementation process, resulting in increased efficiency and transparency in financial management. The study contributes to developing a model for digital financial inclusion in Islamic educational institutions, highlighting the integration of technology with Islamic educational values to improve educational quality holistically.